2019
DOI: 10.1016/j.bja.2019.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Apnoeic oxygenation via nasal cannulae: 15 L min–1 versus high flow

Abstract: that the obese synthetic manikin was equivocally realistic, in that the landmarks were equally difficult to palpate and because it simulated bleeding.Our study demonstrates that this novel 'obese neck' synthetic model reproduces many of the difficulties encountered when performing an eFONA in an obese patient: it performed in a similar fashion to an obese meat-modified model and was more challenging than a traditional 'slim neck' manikin, while avoiding the practical hygiene issues associated with using pork b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…The only directly comparable study is in non-obese older patients which reported similar results. 17 Our findings align with previous studies which report that both flow rate 18 and proximity of fresh gas flow to the respiratory epithelium 19 influence apnoeic oxygenation efficiency.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The only directly comparable study is in non-obese older patients which reported similar results. 17 Our findings align with previous studies which report that both flow rate 18 and proximity of fresh gas flow to the respiratory epithelium 19 influence apnoeic oxygenation efficiency.…”
Section: Discussionsupporting
confidence: 91%
“…Oxygen delivery characteristics may mitigate the risk of desaturation 18 and this study supports this notion. However, the unexpectedly high proportion of patients in the FM group reaching 18 min without desaturation and the wide variability in P a o 2 during apnoea in both groups also suggests that oxygen delivery characteristics are not the primary determinant of whether patients desaturate during apnoea.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Oxygen flow rate at various locations during apnoea has also been investigated. Modelling, simulation and clinical data have all demonstrated that as flow rates increase, so too does apnoea time [8, 15–16].…”
Section: Mechanismsmentioning
confidence: 99%